Laminated foam sheet for thermoforming
The laminated foam sheet achieves easy film peeling and prevents film floating through controlled peeling strength and microbubble formation, enhancing recyclability and appearance.
Patent Information
- Application Number
- JP2021129358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-08-05
AI Technical Summary
Conventional laminated foam sheets face challenges in balancing the ease of peeling off the film without causing film floating and maintaining appearance quality, as increasing adhesion strength to prevent floating makes peeling difficult.
A laminated foam sheet with specific peeling strength and microbubble formation on the peeled surface, using a polystyrene resin foam sheet and thermoplastic resin film, with controlled peeling strength and microbubble area ratio to facilitate easy film removal while preventing film floating.
The laminated foam sheet allows for easy and clean peeling of the film without film floating, maintaining appearance quality and facilitating recycling by simplifying the cleaning process.
Smart Images

Figure 0007621218000004 
Figure 0007621218000005 
Figure 0007621218000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated foam sheet for thermoforming, and more particularly to a laminated foam sheet for thermoforming from which a laminated film can be peeled off. [Background technology]
[0002] A laminated foam sheet is known in which a thermoplastic resin film is laminated and bonded to a polystyrene-based resin foam sheet. Packaging containers such as trays obtained by thermoforming the laminated foam sheet are widely used as food containers for storing cooked foods, etc.
[0003] In recent years, in order to reduce the burden on the environment, efforts have been made to recycle packaging containers by collecting, washing, melting, and pelletizing the packaging containers. However, the collected packaging containers are often dirty, and therefore must be washed at home or at a recycling plant before being recycled. In addition, since the film may be colored, there is a risk that the coloring agent may be mixed into the recycled raw material, causing the recycled raw material to become colored. In order to solve such a problem, a technology has been developed that makes it unnecessary to wash the packaging container by peeling off the film laminated on the polystyrene-based resin foam sheet. For example, there is a packaging container disclosed in Patent Document 1. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 07-96572 Summary of the Invention [Problem to be solved by the invention]
[0005] The laminated foam sheet described in Patent Document 1, and further the molded product obtained by thermoforming, have a low peel strength when peeling the film from the laminated foam sheet in order to make it easier to peel the laminated film. However, in the laminated foam sheet described in Patent Document 1, after thermoforming, the laminated film peels off and floats from the polystyrene-based resin foam sheet, and a phenomenon occurs in which a void is formed at the interface between the polystyrene-based resin foam sheet and the film (hereinafter, also referred to as "film floating"), which may deteriorate the appearance.
[0006] This film lifting can be prevented by increasing the adhesive strength between the film and the polystyrene foam sheet, but increasing the adhesive strength of the film makes it impossible to peel the film from the laminated foam sheet. Therefore, in the conventional techniques, it has been difficult to simultaneously achieve the objectives of peeling the film from the laminated foam sheet and preventing the film from floating. In addition, in the conventional technology, although it is possible to peel off a film from a laminated foam sheet, it may take time to peel off the film, which remains a problem.
[0007] An object of the present invention is to develop a laminated foam sheet for thermoforming which allows easy peeling of a film from the laminated foam sheet, prevents the phenomenon in which the bonded film floats after thermoforming, and has an excellent appearance. [Means for solving the problem]
[0008] According to the present invention, there is provided the following laminated foam sheet for thermoforming. [1] A laminated foam sheet for thermoforming, comprising a polystyrene-based resin foam sheet and a thermoplastic resin film, the thermoplastic resin film being peelably laminated and bonded to at least one surface of the polystyrene-based resin foam sheet, The apparent density of the laminated foam sheet is 50 kg / m 3 More than 200kg / m 3 is as follows: The area of the peeled surface of the polystyrene foam sheet obtained by peeling the film from the laminated foam sheet is 0.002 mm 2The area ratio of the following fine bubbles is 0.5% or more and 20% or less, The laminated foam sheet for thermoforming has an average peel strength of 40 cN / 25 mm or more and 250 cN / 25 mm or less when the thermoplastic resin film is peeled off from the laminated foam sheet. [2] The laminated foam sheet for thermoforming according to the above item 1, wherein the polystyrene-based resin foam sheet is a foam sheet obtained by foaming with an organic physical foaming agent containing a saturated hydrocarbon having 3 to 5 carbon atoms and dimethyl ether. [3] The laminated foam sheet for thermoforming according to item 2, wherein the residual amount of the organic physical foaming agent in the laminated foam sheet is 1.0% by weight or more and 2.5% by weight or less. [4] The laminated foam sheet for thermoforming according to any one of 1 to 3 above, wherein the coefficient of variation of peel strength of the laminated foam sheet is 0.05 or more and 0.15 or less. Effect of the Invention
[0009] In the laminated foam sheet for thermoforming of the present invention, the laminated and bonded thermoplastic resin film can be easily peeled off from the polystyrene-based resin foam sheet. Furthermore, in the laminated foam sheet of the present invention, fine bubbles are formed on the peeled surface of the polystyrene-based resin foam sheet from which the thermoplastic resin film has been peeled off, so that the molded product obtained by thermoforming the laminated foam sheet for thermoforming is prevented from having the laminated thermoplastic resin film float off the polystyrene-based resin foam sheet. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a diagram showing an example of a state in which fine bubbles are formed on the surface of a polystyrene-based resin foamed sheet revealed by peeling a thermoplastic resin film from a laminated foamed sheet. [Diagram 2] FIG. 2 is a photograph showing an example of a molded product in which film lifting 3 is observed. [Diagram 3] FIG. 3 is an explanatory view showing a state in which a thermoplastic resin film is peeled off from the laminated foam sheet of the present invention, and the peeled surface of the polystyrene-based resin foam sheet appears. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The laminated foam sheet for thermoforming of the present invention will be described in detail below. The laminated foam sheet for thermoforming of the present invention (hereinafter also simply referred to as the laminated foam sheet) comprises a polystyrene-based resin foam sheet (hereinafter also simply referred to as the foam sheet) and a thermoplastic resin film (hereinafter also simply referred to as the film), and the film is peelably laminated and adhered to at least one side of the foam sheet.
[0012] In this specification, peelable means that when the film is peeled from the laminated foam sheet, the average peel strength between the foam sheet and the film is 40 cN / 25 mm or more and 250 cN / 25 mm or less, and the film can be peeled from the laminated foam sheet.
[0013] In the present invention, the polystyrene resin foam sheet has a polystyrene resin as a base resin. The polystyrene resin means a resin containing 50% by weight or more of a styrene monomer component unit, and examples thereof include polystyrene, rubber-modified polystyrene (high impact polystyrene), styrene-α-methylstyrene copolymer, styrene-p-methylstyrene copolymer, styrene-acrylic acid copolymer, styrene-methacrylic acid copolymer, styrene-maleic anhydride copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-acrylonitrile copolymer, and a mixture of polystyrene and polyphenylene ether, and may be a mixture of two or more of these polystyrene resins. The polystyrene resin may contain a polyfunctional monomer component unit such as divinylbenzene or a multi-branched macromonomer.
[0014] The base resin may contain other components within the range that does not impair the object of the present invention. Examples of other components include polypropylene resins such as propylene homopolymers and ethylene-propylene copolymers, polyethylene resins such as high-density polyethylene and low-density polyethylene, thermoplastic elastomers such as styrene-conjugated diene block copolymers and their hydrogenated products, and rubbers such as ethylene-propylene rubber and butadiene rubber. The amount of other components contained in the base resin is preferably up to 30% by mass, more preferably 10% by mass or less, and even more preferably 5% by mass or less, and particularly preferably 0% by mass, i.e., consisting of only styrene-based resins.
[0015] The polystyrene resin constituting the foamed sheet has a melt flow rate (MFR) of preferably 0.1 to 5 g / 10 min, more preferably 1 to 3 g / 10 min. By setting the MFR within this range, a foamed sheet having a closed cell structure and excellent mechanical strength can be produced over a wide range of production conditions. In this specification, the melt flow rate refers to the melt mass flow rate measured by Test Method A of JIS K 7210-1 (2014), and the test conditions are a test temperature of 200°C and a load of 5 kg.
[0016] Representative examples of the resin constituting the thermoplastic resin film include polyolefin resins, polystyrene resins, etc. Examples of the polyolefin resins include polyethylene resins such as linear low-density polyethylene, high-density polyethylene, low-density polyethylene, and ethylene-vinyl acetate copolymers, polyethylene resins including biomass-derived polyethylene, polypropylene resins such as propylene homopolymers, ethylene-propylene block copolymers, and ethylene-propylene random copolymers, and polypropylene resins including biomass-derived polypropylene. The polystyrene resin may be the same as the polystyrene resin described above. A multi-layer film in which a plurality of films using these resins are laminated may also be used.
[0017] The thickness of the thermoplastic resin film is preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm, further preferably 15 μm to 35 μm, and particularly preferably 20 μm to 30 μm. If the thickness is within this range, defects such as breakage and holes in the film can be prevented, and the film can be peeled off from the foamed sheet.
[0018] The film may have an adhesive layer for bonding to the polystyrene resin foam sheet. Examples of the adhesive constituting the adhesive layer include conventionally known adhesives such as commonly used acrylic adhesives and urethane adhesives, and conventionally known adhesive resins such as ethylene-vinyl acetate. Also, a so-called adhesive-coated film in which an adhesive is laminated on a resin film may be used.
[0019] Examples of the method for laminating and adhering the film include known methods such as heat lamination, extrusion lamination, etc. Among them, from the viewpoints of ease of operation, the light weight of the resulting molded product, and cost, it is preferable to laminate and adhere the thermoplastic resin film to one or both sides of the foamed sheet by heat lamination.
[0020] The thermal lamination method and the apparatus used for the thermal lamination may be conventionally known.
[0021] In the present invention, the average value of the measured peel strength between the foam sheet and the film when peeling the film from the laminated foam sheet (hereinafter, also referred to as the average peel strength) is 40 cN / 25 mm or more and 250 cN / 25 mm or less. If the peel strength is within this range, the film can be peeled off. In the present invention, even if the average peel strength is such a relatively small value, the occurrence of film lifting in the laminated foam sheet is suppressed. From the viewpoint of ease of peeling, the average peel strength is preferably 50 cN / 25 mm or more and 200 cN / 25 mm or less, more preferably 60 cN / 25 mm or more and 150 cN / 25 mm or less, and even more preferably 70 cN / 25 mm or more and 130 cN / 25 mm or less.
[0022] The peel strength is measured as follows. A test piece with a width of 25 mm is cut from the laminated foam sheet in a direction perpendicular to the extrusion direction, and the film is peeled from the laminated foam sheet in a 90° peel test at a peel speed of 300 mm / min in accordance with JIS Z0237:2009, and the peel strength at that time is measured. The measurement is performed at least 10 times, and the arithmetic average is taken as the average peel strength.
[0023] The coefficient of variation of the peel strength is preferably 0.05 or more and 0.15 or less. The coefficient of variation is a value that indicates the relative variation of the measured peel strength values, and a coefficient of variation of 0.05 or more and 0.15 or less means that the film is laminated and bonded with a more uniform strength. In other words, the smaller the coefficient of variation, the smaller the variation in the individual measured peel strength values. As a method for laminating and bonding with such uniform strength, a method can be adopted in which a film is laminated under conditions in which fine bubbles are formed in the laminated foam sheet, as described below, and the film is laminated and bonded while dispersing and cooling the heat generated during bonding by the generation of the fine bubbles. In this way, it is believed that the variation in peel strength is reduced, and the coefficient of variation is reduced.
[0024] The coefficient of variation is a value obtained by dividing the standard deviation calculated from the individual measured values of peel strength by the arithmetic mean of the individual measured values (the average peel strength), and is calculated by the following formula (1). Cv = ({Σ(Di-Dav) 2 / (n-1)} 1 / 2 ) / Dav) (1) In the formula (1), Di is the measured value of each peel strength, and Dav is the average peel strength.
[0025] In the laminated foam sheet of the present invention, when the film is peeled off from the laminated foam sheet, the area of 0.002 mm 2 The area ratio of the following bubbles (hereinafter also referred to as the fine bubble area ratio) is 0.5% or more and 20% or less.
[0026] The fine bubbles can be formed, for example, by laminating a film by thermal lamination using a foamed sheet formed using a specific organic physical foaming agent described later. It is considered that when the film is laminated and bonded to the foamed sheet by thermal lamination, the surface of the foamed sheet is heated to generate fine bubbles. Then, in the obtained laminated foamed sheet, fine bubbles are observed on the peeled surface of the polystyrene resin foamed sheet obtained by peeling the thermoplastic film from the laminated foamed sheet.
[0027] When the fine bubble area ratio is 0.5% or more, film lifting is unlikely to occur. The reason for this is believed to be that when fine bubbles are generated on the surface of the foamed sheet, the volatilization of the foaming agent near the surface is promoted, making it more difficult for the foaming agent to remain, thereby suppressing the occurrence of film lifting. The film lifting tends to become more severe as the amount of foaming agent is increased in an attempt to produce a foamed sheet with a low apparent density. From this, it is believed that the physical foaming agent remaining in the foamed sheet volatilizes after thermoforming and accumulates at the interface between the foamed sheet and the film, causing the film to lift up and forming spaces.
[0028] In addition, when the fine bubbles are generated, the state of the sheet surface changes and heat is dissipated, so that the adhesion state between the film and the foamed sheet changes in the portion where the fine bubbles are generated, improving the ease of peeling. In particular, the fine bubbles improve the ease of peeling at the beginning stage of peeling the film, making it easier to peel the film.
[0029] On the other hand, if the area ratio of the fine bubbles exceeds 20%, the peel strength is reduced too much, and film lifting may become more likely to occur. From this viewpoint, the fine bubble area ratio is preferably 1% or more and 15% or less, and more preferably 2% or more and 10% or less.
[0030] Fig. 1 shows an example of a state in which fine bubbles are formed on the peeled surface of a foamed sheet that appears when the film of the laminated foamed sheet is peeled off. As shown in Fig. 1, fine bubbles 2 are formed on the peeled surface among normal bubbles 1. Fig. 3 is an explanatory diagram showing the appearance of the peeled surface of the foamed sheet that appears when the film is peeled off from the laminated foamed sheet.
[0031] The fine bubble area ratio was measured by manually peeling off the film from a test piece cut from the center of the width direction of the laminated foam sheet, photographing the peeled surface with a CCD camera or the like to obtain a magnified image, and then measuring the area ratio by 4 mm. 2 The area ratio of the fine bubbles generated in the area of the sample is measured. The area ratio of the fine bubbles is calculated using image editing software as described below.
[0032] Next, various physical properties of the laminated foam sheet for thermoforming of the present invention will be described. The thickness of the laminated foam sheet of the present invention is preferably 0.5 mm or more and 5 mm or less. When the thickness is within this range, the thermoformability of the laminated foam sheet is good, and the container obtained by thermoforming the laminated foam sheet is excellent in rigidity, heat insulation, handleability, etc. From this viewpoint, the thickness is preferably 0.7 mm or more and 4 mm or less, more preferably 1 mm or more and 3 mm or less.
[0033] The thickness of the laminated foam sheet is determined by randomly taking three measurement samples, each 260 mm on a side, from the laminated foam sheet, measuring the thickness of the measurement samples by the above-mentioned method, and arithmetic mean value of the thicknesses.
[0034] The basis weight of the laminated foam sheet is 50 g / m 2 More than 300g / m 2 When the basis weight of the laminated foam sheet is within this range, the laminated foam sheet has excellent lightness while maintaining its rigidity, and the obtained molded article can withstand use as a food packaging container, etc. From this viewpoint, the basis weight is 80 g / m 2 More than 250g / m 2 More preferably, it is 100 g / m or less. 2 More than 200g / m 2 It is even more preferable that:
[0035] In this specification, the basis weight of the laminated foam sheet is measured as follows. First, a test piece measuring 100 mm long x 100 mm wide x the thickness of the laminated foam sheet is cut out from the laminated foam sheet, the weight (g) of the test piece is measured, and the weight is multiplied by 100 to obtain the basis weight (g / m2) by converting the unit. 2 ) is required. The basis weight of a foamed sheet to which no film is laminated can be measured in the same manner as the basis weight of the laminated foamed sheet.
[0036] The apparent density of the laminated foam sheet is 50 kg / m 3 More than 200kg / m 3 If the apparent density is within this range, the strength and light weight of the thermoformed container will be excellent. From this viewpoint, the apparent density is 60 kg / m or less. 3 More than 150kg / m 3 It is preferably equal to or less than 70 kg / m 3 More than 100kg / m 3 The following is the result.
[0037] In this specification, the apparent density of the laminated foam sheet is measured as follows. First, the basis weight (g / m2) of the laminated foam sheet is measured by the above-mentioned method. 2 ) is then calculated. 2 ) by the thickness (mm) of the laminated foam sheet, and convert the value into units to obtain the apparent density (kg / m 3 ) The apparent density of a foamed sheet to which no film is laminated can be measured in the same manner as that of the laminated foamed sheet.
[0038] In the present invention, a cross section of 4 mm that passes through the center of the thickness direction of the laminated foam sheet and is horizontally perpendicular to the thickness direction of the laminated foam sheet is 2 It is preferable that the number of internal bubbles (A) present therein is 100 or less. In addition, the number of bubbles (A) in the peeled surface portion of the polystyrene foam sheet from which the film of the laminated foam sheet has been peeled off is 4 mm 2 It is preferable that the ratio (B / A) of the number of surface bubbles (B) present therein is 1.5 or more and 2.3 or less. A laminated foamed sheet having bubbles within these ranges has an excellent appearance and can be used more suitably as a food container. Furthermore, it can be used well even when the container is wrapped in a plastic wrap or when the container is used in combination with an outer fitting type lid or an inner fitting type lid. From this viewpoint, the cross section perpendicular to the thickness direction of the laminated foam sheet is 4 mm 2 The number of internal bubbles (A) present therein is preferably 80 or more and 95 or less, and more preferably 85 or more and 93 or less.
[0039] The number of bubbles present in a cross section of the laminated foam sheet cut along the thickness direction (number of bubbles in a vertical cross section) is preferably 10 to 25, more preferably 15 to 20. The longitudinal cross-section bubble count is determined by photographing a cross section of a laminated foam sheet cut in a direction perpendicular to the extrusion direction and in the thickness direction at 10 equally spaced locations in the width direction with a microscope or the like to obtain enlarged images. Next, a line l is drawn in the thickness direction of each cross-section photograph, and the number n of all bubbles in the foam sheet that intersect with the line l is counted. The average of the bubble counts thus obtained is regarded as the average bubble count in the thickness direction of the laminated foam sheet.
[0040] The laminated foam sheet of the present invention has a closed cell ratio of 60% or more. If the closed cell ratio is too small, the rigidity and thermoformability of the resulting container may decrease. In addition, the rigidity of the container may decrease. From this viewpoint, the closed cell ratio is preferably 70% or more, more preferably 80% or more.
[0041] In this specification, the closed cell ratio of a laminated foam sheet or a foam sheet is measured as follows: According to procedure C of ASTM-D2856-70, a Toshiba Beckman air-comparison specific gravity meter Model 930 is used to measure (a laminated foam sheet or a foam sheet is randomly cut into cut samples measuring 25 mm × 40 mm × sheet thickness, and a plurality of cut samples are stacked and placed in a sample cup so that the total thickness of the samples is as close as possible to 20 mm (but does not exceed 20 mm) and measured) the true volume Vx of the laminated foam sheet or the foam sheet (cut sample) is calculated using the following formula (2) to calculate the closed cell ratio S (%), which is the average value of n=5. S(%)=(Vx-W / ρ)×100 / (Va-W / ρ) ···(2)
[0042] Vx: The true volume (cm) of the cut sample measured by the above method 3 ) and corresponds to the sum of the volume of the resin constituting the laminated foam sheet or foam sheet and the total volume of the air bubbles in the closed cell portion in the cut sample. Va: Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ). W: total weight of cut sample used for measurement (g). ρ: Density of the laminated foam sheet or the resin that composes the foam sheet (g / cm 3 )
[0043] Next, the remaining amount of the organic physical foaming agent in the laminated foam sheet of the present invention will be described. The remaining amount of the organic physical foaming agent in the laminated foam sheet is preferably 1.0% by weight or more and 2.5% by weight or less. If the remaining amount is within this range, desirable secondary foaming occurs during molding in the mold, a molded product having the shape of the mold can be obtained, and film lifting after thermoforming can be prevented. For these reasons, the remaining amount is more preferably 1.2% by weight or more and 2.3% by weight or less, and even more preferably 1.5% by weight or more and 2.1% by weight or less. By going through the film lamination process by thermal lamination, the remaining amount of the foaming agent in the laminated foam sheet becomes less than the foaming agent content in the foam sheet.
[0044] If the remaining amount is within this range, it is easy to peel the film from the laminated foam sheet and prevent film lifting. In order to prevent film lifting, the smaller the remaining amount, the better. On the other hand, in order to achieve good thermoformability, it is necessary for the organic physical foaming agent to remain in the foam sheet and contribute to secondary foaming during thermoforming. Therefore, as described above, it is desirable that an amount of the organic physical foaming agent remaining in the foam sheet constituting the laminated foam sheet is sufficient to prevent film lifting.
[0045] Next, the physical properties of the foamed sheet used in the production of the laminated foamed sheet of the present invention will be described. The apparent density of the foamed sheet is 50 kg / m 3 More than 200kg / m 3 If the apparent density is within this range, the molded article obtained by thermoforming the obtained laminated foam sheet will have excellent strength and light weight. From this viewpoint, the apparent density is preferably 60 kg / m or less. 3 More than 150kg / m 3 It is preferably equal to or less than 65 kg / m 3 More than 100kg / m3 The apparent density of the foamed sheet can be measured in the same manner as that of the laminated foamed sheet.
[0046] The thickness of the foamed sheet is preferably 0.5 mm or more and 5 mm or less. When the thickness is within this range, the molded article obtained by thermoforming the laminated foamed sheet obtained by laminating and bonding a film to the foamed sheet has excellent rigidity, heat insulation, handleability, etc., and can be suitably used as various containers. From this viewpoint, the thickness is preferably 0.7 mm or more and 4 mm or less, more preferably 1 mm or more and 3 mm or less. The thickness of the foamed sheet can be measured in the same manner as the measurement method for the laminated foamed sheet.
[0047] The foam sheet has a basis weight of 50 g / m 2 More than 250g / m 2 When the basis weight of the foamed sheet is within this range, a molded article obtained by thermoforming a laminated foamed sheet obtained from the foamed sheet can withstand use as a food packaging container, etc. From this viewpoint, the basis weight is 80 g / m 2 More than 200g / m 2 More preferably, it is 100 g / m or less. 2 More than 150g / m 2 The basis weight of the foamed sheet can be measured in the same manner as that of the laminated foamed sheet.
[0048] Next, the content of the organic physical foaming agent in the foamed sheet used for producing the laminated foamed sheet will be described. The content of the organic physical foaming agent in the foam sheet used for producing the laminated foam sheet is preferably 1.5% by weight or more and 3% by weight or less. If the content is within this range, desirable secondary foaming occurs during in-mold molding of the obtained laminated foam sheet, and the polystyrene resin is plasticized, so that a molded product having the shape of the mold can be obtained, and the film lifting phenomenon after thermoforming can be prevented. For these reasons, the content is more preferably 1.8% by weight or more and 2.8% by weight or less, and even more preferably 1.9% by weight or more and 2.5% by weight or less.
[0049] In order to obtain a laminated foamed sheet having a residual amount of foaming agent within the above range, it is preferable to use, as the organic physical foaming agent used in the production of the foamed sheet, an organic mixture physical foaming agent containing an aliphatic hydrocarbon having 3 to 5 carbon atoms and an early dissipative foaming agent.
[0050] Since the aliphatic hydrocarbons having 3 to 5 carbon atoms have a relatively slow volatilization rate from the foamed sheet and a slower permeation rate into the polystyrene resin than air, the secondary foaming property and plasticization of the foamed sheet in thermoforming can be ensured for a long period of time, and the life cycle of the obtained laminated foamed sheet can be extended. For these reasons, butane is more preferably used, and isobutane is even more preferably used. On the other hand, the early dissipative blowing agent may be one that has a faster permeation rate through polystyrene resin than air. For example, ethers with a boiling point of 140°C or less, dialkyl carbonates with a boiling point of 140°C or less, alcohols, carbon dioxide, water, etc. are included. Among these, ethyl methyl ether, dimethyl ether, and diethyl ether are preferred. Dimethyl ether is more preferred because it is easy to produce a foamed sheet with a low apparent density and can sufficiently plasticize polystyrene resin. The permeation rate of dimethyl ether through polystyrene resin is 77 times that of normal butane, and the permeation rate of isobutane is 0.1 times that of normal butane. Therefore, when a foamed sheet is produced using a mixed foaming agent of dimethyl ether, normal butane, and isobutane, dimethyl ether contributes to reducing the apparent density but volatilizes early, whereas normal butane and isobutane, especially isobutane, remain in the foamed sheet for a long period of time and contribute to improving thermoformability.
[0051] When dimethyl ether is used, the bubbles inside the foamed sheet tend to become larger. Therefore, the number of internal bubbles (A) tends to be small, so the ratio of the number of bubbles (A) to the foamed sheet side peeled surface 4 mm from which the film of the laminated foamed sheet is peeled is 2 It is more preferable that the ratio (B / A) of the number of surface bubbles (B) present therein is 1.8 or more and 2.8 or less. The reason why the bubbles inside the foamed sheet become large is believed to be that the high rate of permeation of dimethyl ether through the cell walls increases the rate of bubble growth in the initial stage of foaming.
[0052] The remaining amount (wt%) of the organic physical blowing agent in the laminated foam sheet and the content (wt%) of the organic physical blowing agent in the foam sheet can be measured by the internal standard method using a gas chromatograph. Specifically, a sample of about 1 g is cut out from the center of the entire width of the laminated foam sheet or the foam sheet, and immediately put into toluene containing an internal standard substance in a lidded sample bottle, and after closing the lid, the solution is thoroughly stirred to dissolve the blowing agent in the sample in toluene, and the solution is used as a measurement sample to perform gas chromatographic analysis to determine the content of the organic physical blowing agent.
[0053] By the above-mentioned method, the content (wt%) of saturated hydrocarbons in the laminated foam sheet and the foam sheet can be obtained. Also, the content (wt%) of dimethyl ether in the laminated foam sheet and the foam sheet can be obtained.
[0054] The amount of dimethyl ether remaining in the laminated foam sheet is preferably 1% by weight or less, more preferably 0.5% by weight or less, 0.3% by weight or less, further preferably 0.1% by weight or less, and particularly preferably 0.05% by weight or less.
[0055] Next, the method for producing the laminated foam sheet of the present invention will be described. The laminated foam sheet of the present invention can be obtained by forming a foam sheet by a conventionally known so-called extrusion foaming method, and laminating and adhering a thermoplastic resin film to the foam sheet. Specifically, it can be produced, for example, as follows.
[0056] First, a polystyrene-based resin foam sheet is produced. Specifically, a polystyrene-based resin and a bubble regulator such as talc, which is added as necessary, are fed to an extruder, and heated, melted, and kneaded to form a molten resin. Next, a physical foaming agent is pressed into the molten resin, which is further kneaded and adjusted to a foamable resin temperature to form a foamable resin melt. Next, the foamable resin melt is introduced into an annular die attached to the downstream side of the extruder, and extruded and foamed into the atmosphere to form a cylindrical foam. Next, the cylindrical foam is cut open while being pulled along a cylindrical cooling device to obtain a foam sheet.
[0057] As the foaming agent for obtaining the foamed sheet used in the present invention, as described above, an organic physical foaming agent containing an aliphatic hydrocarbon having 3 to 5 carbon atoms and an early dissipating foaming agent is preferably used. As the aliphatic hydrocarbon having 3 to 5 carbon atoms, normal butane, isobutane, and mixed butane of normal butane and isobutane are preferred, since they have a slow dissipation rate from the foamed sheet and can ensure the secondary foaming property of the foamed sheet in thermoforming for a long period of time, and isobutane is more preferred.
[0058] On the other hand, as the early dissipation foaming agent, dimethyl ether is preferred because it is easy to produce a foamed sheet with a low apparent density, it can sufficiently plasticize polystyrene resin, etc. Furthermore, by using an early dissipation foaming agent, the amount of residual foaming agent in the laminated foamed sheet can be reduced, and film lifting can be effectively suppressed. The total amount of the organic physical foaming agent is preferably 1 to 8 parts by weight, and more preferably 2 to 5 parts by weight, based on 100 parts by weight of the polystyrene resin.
[0059] Hereinafter, a case where isobutane and dimethyl ether are used in combination as an organic physical blowing agent will be described. However, the present invention is not limited to this combination, and other saturated hydrocarbons having 3 to 5 carbon atoms and early dissipation blowing agents can be used. Also, one or more saturated hydrocarbons having 3 to 5 carbon atoms and one or more early dissipation blowing agents may be used in combination.
[0060] The amount of isobutane is preferably 1 to 4 parts by weight based on 100 parts by weight of the polystyrene resin. By using isobutane in an amount within the above range, a foamed sheet having a desired thickness and apparent density can be easily formed. In addition, a foamed sheet having excellent moldability, particularly excellent secondary foamability and excellent moldability into a mold can be obtained. From this viewpoint, the amount is more preferably 2 to 3.5 parts by weight.
[0061] The amount of dimethyl ether is preferably 0.5 to 2 parts by weight based on 100 parts by weight of polystyrene resin. Dimethyl ether has a high dissipation rate from the foamed sheet, so by using dimethyl ether as a physical foaming agent, the polystyrene resin can be sufficiently plasticized during the production of the foamed sheet, while contributing to a low apparent density of the foamed sheet. In addition, the amount of the foaming agent remaining in the resulting foamed sheet can be reduced, so that the laminated foamed sheet obtained by laminating a film on the resulting foamed sheet is one in which film lifting after thermoforming is suppressed. From this viewpoint, the amount is preferably 0.6 to 1.8 parts by weight, more preferably 0.8 to 1.5 parts by weight.
[0062] In addition, when a mixed foaming agent of isobutane and dimethyl ether is used as the physical foaming agent, the weight ratio of isobutane to dimethyl ether is preferably 55:45 to 80:20. By setting the weight ratio within this range, a foamed sheet that has excellent thermoformability and can be used to produce a laminated foamed sheet that can prevent the film lifting phenomenon can be obtained. From this viewpoint, the weight ratio is more preferably 60:40 to 75:25.
[0063] In the present invention, various additives such as a cell regulator, a colorant such as a pigment or a dye, a heat stabilizer, a filler, etc. may be appropriately blended with the base resin as required.
[0064] As the bubble regulator, for example, inorganic powders such as talc, kaolin, mica, silica, calcium carbonate, barium sulfate, titanium oxide, aluminum oxide, clay, bentonite, diatomaceous earth, and conventionally known chemical foaming agents such as azodicarbodiamide can be used. Among them, talc is preferable from the viewpoint of handling and cost. The amount of the bubble regulator to be added varies depending on the type of the bubble regulator, the target bubble diameter, and the like, but is preferably about 0.01 to 8 parts by weight, more preferably 0.02 to 5 parts by weight, and particularly preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the base resin.
[0065] Next, a method for laminating and adhering a film to a foamed sheet will be described. The method for laminating and adhering the thermoplastic resin film to the obtained foamed sheet includes known methods such as heat lamination, extrusion lamination, etc. Among them, it is preferable to laminate and adhering the thermoplastic resin film to one or both sides of the foamed sheet by heat lamination, since it is easy to adjust the average peel strength and it is easy to generate fine bubbles.
[0066] The lamination of a film onto a foamed sheet by thermal lamination is usually carried out by first winding up the foamed sheet that has been extrusion-foamed and taken up into a roll, and then unwinding the foamed sheet from the roll in a process separate from the foaming process, overlaying the film, and passing the laminate through a thermal lamination device (offline processing). However, a method may also be adopted in which a film is superimposed on an extrusion-foamed foam sheet on a foam sheet production line, the film is passed through a thermal lamination device to form a laminated foam sheet, and the laminated foam sheet is then wound up into a roll (online processing).
[0067] In the thermal lamination, for example, a thermal lamination device having a heating roll and a pressure roll capable of pressing a foam sheet is used, and the film and the foam sheet are overlapped and fed between the heating roll and the pressure roll so that the film is in contact with the heating roll, and the film and the foam sheet are sandwiched together, thereby laminating and adhering the film to the foam sheet.
[0068] When obtaining the laminated foam sheet of the present invention, the peel strength can be adjusted by changing the heating conditions during adhesion of the foam sheet and the film, the line speed, etc., for example by setting the temperature of the heating roll to 155 to 190°C, particularly preferably 158 to 180°C.
[0069] The thermal lamination method and the device used for the thermal lamination may be any of the conventionally known methods.
[0070] The laminated foam sheet of the present invention has excellent thermoformability, and can be thermoformed to obtain molded articles having various shapes formed into a mold.
[0071] Thermoforming methods include vacuum forming, compressed air forming, and their applications such as free drawing, plug and ridge forming, ridge forming, matched mold forming, straight forming, drape forming, reverse draw forming, air slip forming, plug assist forming, plug assist reverse draw forming, and combinations of these. Such thermoforming methods are preferred because they can produce molded bodies continuously in a short time. When thermoforming a laminated foam sheet laminated and bonded with a film having excellent oil resistance, such as a polyolefin resin film, it is preferable to mold the film so that the thermoplastic resin film having excellent oil resistance is located on the inside of the molded body obtained.
[0072] The molded articles obtained by thermoforming are used as various food containers, including containers for natto and food trays. After using these containers, the cleaning process can be simplified by peeling off only the film, thereby improving the recyclability of the foam sheet. Furthermore, the film can be peeled off from the sheet remaining after the molded body is punched out, which is generated during the molding of the laminated foam sheet, in the same manner as from the molded body, further improving the recyclability of the laminated foam sheet of the present invention. EXAMPLES
[0073] The present invention will be described in detail below with reference to examples, although the present invention is not limited to these examples.
[0074] In the examples and comparative examples, the following equipment was used. As an apparatus for forming a foamed sheet, a tandem type extruder in which a first single-screw extruder having an inner diameter of 115 mm and a second single-screw extruder having an inner diameter of 180 mm were connected in series was used. The thermal lamination device used was equipped with a heating roll (upper side) and a clamping roll (lower side) capable of pressing the foam sheet and film together, and two upper and lower cooling rolls capable of pressing and cooling the laminated foam sheet consisting of a foam sheet (lower side) and a film (upper side).
[0075] The various raw materials used in the examples and comparative examples are as follows.
[0076] (Polystyrene resin) (1) Abbreviated name "Resin 1": Polystyrene resin manufactured by PS Japan Co., Ltd.: Product name "GX154" (MFR 1.5g / 10min)
[0077] Foam regulator: Talc "Matsumura Sangyo High Filler #12" master batch (talc 35% by weight)
[0078] Organic Physical Blowing Agent (1) Isobutane (2) Dimethyl ether
[0079] (Thermoplastic resin film) (1) Abbreviation "CPP": Sun-Tox Co., Ltd. non-oriented polypropylene film "KT" (thickness 25 μm) (2) Abbreviation "CPS": Styrofoam SPH (thickness 25 μm) manufactured by Oishi Sangyo Co., Ltd.
[0080] Examples 1 to 3, Comparative Examples 1 to 5 The type and amount of polystyrene resin shown in Table 1 and the amount of talc (cell foam regulator: Matsumura Sangyo Co., Ltd. Hi-filler #12) shown in Table 1 were fed to the first extruder of the tandem extruder, heated, melted, and kneaded, and the type and amount of organic physical foaming agent shown in Table 1 was pressed into the amount shown in Table 1 per 100 parts by weight of the polystyrene resin, further kneaded, and transferred to the second extruder, where the extrusion resin temperature was adjusted to 145°C to obtain a foamed sheet-forming resin melt. The foamed sheet-forming resin melt was extruded and foamed into the atmosphere from the annular die at a discharge rate of 300 kg / hr to form a foamed cylindrical body, and immediately thereafter, 23°C air was blown at a volume of 3.0 m3 onto the inside of the foamed cylindrical body (the mandrel surface side (M surface side)). 3The foamed cylindrical body was then drawn along the outer surface of a cooling cylinder (mandrel) with an outer diameter of 670 mm at a speed of 17 m / min. While the body was being drawn along the outer surface of the cooling cylinder (mandrel) with an outer diameter of 670 mm at a speed of 17 m / min, it was cut open into two pieces along the extrusion direction and wound up to obtain two foamed sheets (width 1050 mm).
[0081] The physical foaming agents were injected using independent diaphragm pumps, with the gas flow rate (weight of gas injected per hour) set for each, and injected simultaneously into the molten resin. The amount of foaming agent mixed was calculated from the total discharge rate (kg / hr) and the amount of gas injected for each (kg / hr).
[0082] The foamed sheet thus obtained was measured for basis weight, thickness, apparent density, foaming agent content and fine bubble area ratio. The results are shown in Table 1.
[0083] [Table 1]
[0084] Next, the obtained foamed sheet was cured at room temperature, and 20 days after production, a film was laminated and bonded to the S-side of the foamed sheet (the side opposite to the M-side, which was the side taken up along the mandrel) by thermal lamination. In the thermal lamination, the above-mentioned device was used to laminate and bond a film shown in Table 2 to one side of the foamed sheet under thermal lamination conditions of a heating roll having a heating temperature shown in Table 2, a pinch clearance of 0.3 mm, and a line speed shown in Table 2.
[0085] After the thermal lamination, the product was cured in an indoor environment (23°C, relative humidity 50%), and after 24 hours, it was thermoformed using a rectangular tray mold measuring 100 mm x 185 mm x 18 mm in height to obtain a tray-shaped molded product.
[0086] The physical properties of the obtained laminated foam sheet, such as the thickness, are shown in Table 2.
[0087] [Table 2]
[0088] In the laminated foam sheets obtained in Examples 1 to 3, the film could be peeled off from the laminated foam sheets, and the generation of appropriate fine bubbles was confirmed, and the effect of preventing the film from lifting was also confirmed. In addition, the ease of peeling off the film was improved, and the laminated foam sheets obtained were particularly easy to peel off from.
[0089] Comparative Example 1 is an example in which only butane was used as the foaming agent, and the amount of residual foaming agent was large, so the problem of film lifting could not be solved. Comparative Example 2 is an example in which the blending weight ratio of butane and dimethyl ether was 50:50. The film was easy to peel off, but too many fine bubbles were generated, reducing the peel strength and causing film lifting. Comparative Example 3 is an example in which only butane was used as the foaming agent and the amount of the bubble adjusting agent was changed, similarly to Comparative Example 1. Fine bubbles were not generated during thermal lamination, and film lifting occurred. Comparative Example 4 is an example in which the blending weight ratio of butane and dimethyl ether was 90:10. The amount of fine bubbles generated was small, and film lifting occurred. Comparative Example 5 is an example in which the foam sheet and the film are bonded together beyond the range of peel strength that allows peeling. Although the film is prevented from lifting and fine bubbles are generated, the peel strength of the laminated foam sheet is too high, making it difficult to peel the film. Therefore, it is understood that the effect of facilitating film peeling at the start of peeling is exhibited when the average peel strength of the laminated foam sheet is in a relatively low range.
[0090] Next, the measurement method of each physical property value in the table and the evaluation method of each evaluation will be described.
[0091] (Thickness of foam sheet, laminated foam sheet) The thickness of the foam sheet and the laminated foam sheet was measured by randomly taking three measurement samples with sides of 260 mm from the foam sheet and the laminated foam sheet, measuring the thickness of the measurement samples using the above-mentioned method, and taking the arithmetic average value (n=3) as the thickness.
[0092] (Basis weight of foam sheet, laminated foam sheet) The basis weight of the foam sheet or laminated foam sheet was measured by the above-mentioned method. Specifically, three rectangular test pieces of 100 mm were cut out across the entire width of the foam sheet or laminated foam sheet. The weight (g) of the test piece was divided by the area of the test piece (sheet width (mm) x 100 mm) to obtain the basis weight per 1 m 2 The arithmetic average value is calculated as the basis weight (g / m2) of the foam sheet, laminated foam sheet, etc. 2 ) was decided.
[0093] (Apparent density of laminated foam sheet and foam sheet) The apparent density of the laminated foam sheet was measured by the above-mentioned method. First, the basis weight (g / m 2 ) was obtained. Next, the basis weight (g / m 2 ) by the thickness (mm) of the laminated foam sheet, and convert the value into units to obtain the apparent density (kg / m 3 The foamed sheet was also measured in the same manner.
[0094] (Laminated foam sheet, microbubble area ratio of foam sheet) The area ratio of fine bubbles in the laminated foam sheet was measured by cutting a test piece from the center of the laminated foam sheet in the width direction, peeling off the film by hand, and photographing the peeled surface of the foam sheet that was revealed with a CCD camera at a magnification of 200 times. 2 Select the part of 4 mm 2 Within the portion, the fine cell portion was marked, and the image was binarized using image editing software so that only the image after marking emerged, and the area ratio of the marked portion was calculated as the percentage of pixels. In the above measurement, the fine bubbles have an area of 0.002 mm 2 The bubbles had the following bubble areas: Regarding the area ratio of fine bubbles in the foamed sheet, the surface of the foamed sheet on which the film was to be laminated was observed with a CCD camera, and the fine bubbles were similarly observed.
[0095] (Average bubble area of laminated foam sheet) The average bubble area of the laminated foam sheet was measured by cutting out a test piece from the center of the width direction of the laminated foam sheet, peeling off the film by hand, and observing the surface of the foam sheet with a CCD camera. 2 The area of the bubble portion excluding the fine bubble portion was measured for the area of the above-mentioned portion. The area was calculated in the same manner as described above.
[0096] (Residual amount of foaming agent in laminated foam sheet, foaming agent content in foam sheet) The residual amount (wt%) of the foaming agent in the laminated foam sheet was measured by the internal standard method using a gas chromatograph. Specifically, a sample of about 1 g was cut out from the center of the entire width of the laminated foam sheet, and immediately put into toluene containing an internal standard substance in a lidded sample bottle, and after closing the lid, the solution was thoroughly stirred to dissolve the foaming agent in the laminated foam sheet in toluene. The solution was used as a measurement sample and analyzed by gas chromatography (GC-4000 manufactured by GL Science Co., Ltd.) to determine the content ratio of the foaming agent. In the case of the laminated foam sheet, the weight of the film was subtracted to determine the remaining amount of the foaming agent in the foam sheet constituting the laminated foam sheet. The content of the foaming agent in the foam sheet was measured immediately after the foam sheet was produced. Meanwhile, the remaining amount of the foaming agent in the laminated foam sheet was measured 14 days after the laminated foam sheet was produced. In addition, isobutane, which is a saturated hydrocarbon having 3 to 5 carbon atoms, and dimethyl ether, which dissipates quickly, were measured separately, and the total amount was taken as the remaining amount and content of the blowing agent.
[0097] (Average peel strength of laminated foam sheet, coefficient of variation of measured peel strength) The peel strength was measured for 20 samples by the above-mentioned method, and the average peel strength and the coefficient of variation were calculated.
[0098] (Peel strength of molded body) Ten samples were taken from the flat bottom surface of the obtained molded article, and the average peel strength of the molded article was measured by the above-mentioned method.
[0099] (Ease of peeling off the film) The laminated foam sheet was cut into 100 mm squares using a cutter, and three people peeled the film off from the edge of the cut surface with their fingers. The ease of peeling, particularly when starting to peel the film, was evaluated using the following method. ○: The average score of the three reviewers is 2.0 or more. ×: The average score of the three reviewers is less than 2.0 points Evaluation points 3. You can easily start peeling off the film. 2 points: It is possible to start peeling the film within an average of 10 seconds. 1 point: You can start to peel off the film by carefully scratching the cut edge with your fingernail, but it takes an average of more than 10 seconds to start peeling.
[0100] (Film floating) The laminated foam sheet was thermoformed into a tray-shaped molded product, and after 30 days, the molded product was evaluated based on whether or not gaps were observed at the interface between the film on the surface of the molded product and the foam sheet (film lifting was observed). ○: No film lifting is observed △: Small gaps are visible in the uneven parts of the bottom surface. ×: Film lifting is clearly visible
[0101] The laminated foam sheets obtained in the Examples and Comparative Examples were measured for the number of cells in the longitudinal section, the number of cells on the surface, and the number of cells inside. The results are shown in Table 3.
[0102] [Table 3]
[0103] In Table 3, each item was measured as follows. (Vertical cross section bubble count) The cross sections of the laminated foam sheet perpendicular to the extrusion direction were photographed with a microscope at 10 equally spaced locations in the width direction. Next, a line l was drawn in the thickness direction of each cross-sectional photograph, and the number of bubbles n in the foam sheet that intersected with the line l was counted. The average of the bubble counts thus obtained was taken as the average bubble number in the thickness direction of the foam sheet.
[0104] (Number of surface bubbles B) On the surfaces (S and M surfaces) of the laminated foam sheet, 2 The area of 4 mm was observed using a CCD camera. 2 The number of bubbles (excluding fine bubbles) present within the range was counted.
[0105] (Number of internal bubbles A) The number of bubbles in the center of the longitudinal section of the laminated foam sheet (the number of internal bubbles (A)) is the number of bubbles in the central 4 mm area excluding the area 200 μm from the surface in a cross section of the laminated foam sheet cut in the thickness direction. 2 The area of 4 mm was observed using a CCD camera. 2 The number of bubbles present within the range was counted. [Explanation of symbols]
[0106] 1 Normal bubbles 2. Microbubbles 3 Film floating 4. Thermoforming laminated foam sheet 5 Polystyrene resin foam sheet 6 Thermoplastic Film 7 Peeling Surface
Claims
1. A laminated foam sheet for thermoforming, comprising a polystyrene-based resin foam sheet and a thermoplastic resin film, the thermoplastic resin film being peelably laminated and bonded to at least one surface of the polystyrene-based resin foam sheet, The apparent density of the laminated foam sheet is 50 kg / m 3 More than 200kg / m 3 is as follows: The area of the peeled surface of the polystyrene-based resin foam sheet obtained by peeling the thermoplastic resin film from the laminated foam sheet is 0.002 mm 2 The area ratio of the following fine bubbles is 0.5% or more and 20% or less, The laminated foam sheet for thermoforming has an average peel strength of 40 cN / 25 mm or more and 250 cN / 25 mm or less when the thermoplastic resin film is peeled off from the laminated foam sheet.
2. 2. The laminated foam sheet for thermoforming according to claim 1, wherein the polystyrene-based resin foam sheet is a foam sheet foamed with an organic physical foaming agent containing a saturated hydrocarbon having 3 to 5 carbon atoms and dimethyl ether.
3. 3. The laminated foam sheet for thermoforming according to claim 2, wherein the residual amount of the organic physical foaming agent in the laminated foam sheet is 1.0% by weight or more and 2.5% by weight or less.
4. The laminated foam sheet for thermoforming according to any one of claims 1 to 3, wherein the coefficient of variation of peel strength of the laminated foam sheet is 0.05 or more and 0.15 or less.
Citation Information
Patent Citations
Foamed thermoplastic sheet coated with releasable thermoplastic film, production thereof, and molded article thereof
JP1995096572A
Thermoplastic resin laminated foamed sheet for forming top sealed container and container with flange for top sealing
JP2001162734A
Polystyrene-base resin foamed plate for display panel core material and display panel
JP2002215072A
Heat insulating panel
JP2006123178A
Polystyrene resin multilayer foam sheet
JP2019111785A